Institutional spillovers from the negotiation and formulation of East Asian free trade agreements: Government-business relations in the policymaking of bilateral free trade agreements - Antonio Postigo (Review of International Political Economy, 2016)
East Asian countries have implemented around 60 free trade agreements (FTAs), mostly bilateral, to become one of the most active sites of regionalism. The dominant analyses portray these FTAs as driven primarily by foreign policy motivations and promoted by political leaders with businesses marginally involved or interested. It is contended here that, compared to other forms of liberalization, bilateral FTA negotiations promote new institutional arrangements within government agencies and business associations and unique configurations of government-business relations. Formulation of FTAs imposes greater information demands on government officials, which should compel them to consult business associations. In turn, clearer identification of FTAs' impacts and greater chances to affect their formulation should increase business incentives to lobby for or against FTA liberalization domestically and across borders. Demands on officials and business associations upon successive FTAs should foster institutional change/creation to reduce information and coordination costs. These hypotheses were tested on the bilateral FTAs of Thailand and Malaysia. FTAs in these countries stimulated government-business consultations and lobbying by businesses that, for some key FTAs, took the initiative. Successive negotiations strengthened the technical capacities of officials and business associations and stimulated the emergence of new institutions, which may endure to provide similar functions for multilateral rounds.
Keywords: 330